Cellular and molecular mechanism of ofloxacin induced apoptotic cell death under ambient UV-A and sunlight exposure. (March 2014) - Dwivedi, A.; Mujtaba, S. F.; Yadav, N.; Kushwaha, H. N.; Amar, S. K.; Singh, S. K.; Pant, M. C.; Ray, R. S.
Abstract Ofloxacin (OFLX) is a racemic mixture of levofloxacin which revealed phototoxicity in patients exposed with sunlight after medication. Here, we have been addressed the possible cellular and molecular mechanisms of OFLX induced apoptosis under ambient UV-A and sunlight exposure using HaCaT cell line as a model. The results showed that Photodegradation and three photo-products formation of OFLX by LC-MS/MS under ambient intensities of UV-A (1.5 and 2.2 mW/cm2) and sunlight. OFLX produced 1O2, O2.−, and OH radicals via type-II- and type-I-dependent reaction mechanism, which corroborated by its specific quenchers. 2'-dGua degradation in photochemical and % tail DNA formation in cell line using comet test advocated the genotoxic potential of OFLX. Photocytotoxic assays (MTT and NRU) revealed the considerable decline in cell viability by OFLX. OFLX triggered apoptosis, proved by cell cycle, Annexin V/PI double staining along with acridine orange (AO)/ethidium bromide (EB), and Hoechst staining as well as caspase-3 activity by colorimetric assay. OFLX induced lysosomal disruption and mitochondrial membrane destabilization confirmed through fluorescence staining with AO/JC-1. OFLX significantly upregulated the expression of p21 and bax genes. In conclusion, the study revealed that photosensitized OFLX induced apoptosis via ROS-mediated DNA damage, destabilization of lysosomal and mitochondrial membrane, and upregulation of p21, bax, and caspase-3 genes.